Photosymbiosis in planktonic foraminifera across the Paleocene–Eocene thermal maximum. Issue 4 (November 2021) - Shaw, Jack O.; D'haenens, Simon; Thomas, Ellen; Norris, Richard D.; Lyman, Johnnie A.; Bornemann, André; Hull, Pincelli M.
Abstract: Under stress, corals and foraminifera may eject or consume their algal symbionts ("bleach"), which can increase mortality. How bleaching relates to species viability over warming events is of great interest given current global warming. We use size-specific isotope analyses and abundance counts to examine photosymbiosis and population dynamics of planktonic foraminifera across the Paleocene–Eocene thermal maximum (PETM, ~56 Ma), the most severe Cenozoic global warming event. We find variable responses of photosymbiotic associations across localities and species. In the NE Atlantic (DSDP Site 401) PETM, photosymbiotic clades (acarininids and morozovellids) exhibit collapsed size-δ 13 C gradients indicative of reduced photosymbiosis, as also observed in Central Pacific (ODP Site 1209) and Southern Ocean (ODP Site 690) acarininids. In contrast, we find no significant loss of size-δ 13 C gradients on the New Jersey shelf (Millville) or in Central Pacific morozovellids. Unlike modern bleaching-induced mass mortality, populations of photosymbiont-bearing planktonic foraminifera increased in relative abundance during the PETM. Multigenerational adaptive responses, including flexibility in photosymbiont associations and excursion taxon evolution, may have allowed some photosymbiotic foraminifera to thrive. We conclude that deconvolving the effects of biology on isotope composition on a site-by-site basis is vital for environmental reconstructions.